Natural gas hydrates a guide for engineers - Carroll, John J., 1958- (Gulf Professional Pub., 2003)
This is the most exhaustive study to date on natural gas hydrates. In spite of their importance, hydrates are misunderstood, and misconceptions abound. This book provides an accurate review of what hydrates are and under what conditions they will form, and it provides the engineer with the methods to predict the occurrences of hydrates. The petroleum industry spends millions every year to combat the formation of hydrates, the solid, crystalline compounds that form from water and small molecules, damaging equipment and plugging transmission lines. Understanding how, when, and where they form and using this knowledge to apply remedies in practical applications are crucial. The most comprehensive study of natural gas hydrates A manual for the engineer or textbook for the student Contains cutting-edge solutions to natural gas hydrate problems.